2016
DOI: 10.15517/revenf.v0i32.27214
|View full text |Cite
|
Sign up to set email alerts
|

Dolor al administrar medicamento por inyección intramuscular: ventroglútea vs dorsoglútea

Abstract: Introducción. La inyección intramuscular es una técnica que causa dolor e incomodidad a las personas. Con el objetivo de determinar la zona de punción menos dolorosa para la administración de medicamentos intramusculares en glúteo, se realizó una revisión de literatura en busca de la evidencia de mayor calidad. Método. Se empleó el método propuesto por el enfoque de la Práctica Clínica de Enfermería Basada en la Evidencia. Se recopiló estudios de EBSCOhost, Google, Google Académico, Cochrane Library y PubMed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…However, the results of this study reported no difference between patients’ pain levels based on gender. Most of the studies in the literature related to pain during IM injection which compared pain levels according to IM injection sites (Güneş et al, 2013; Kara, 2013; Kilic et al, 2014; Rodríguez et al, 2017; Tuğrul & Khorshıd, 2014; Yilmaz et al, 2016) and many of these studies did not compare pain according to gender. Results similar to the findings of the present study were obtained in the limited number of comparison studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of this study reported no difference between patients’ pain levels based on gender. Most of the studies in the literature related to pain during IM injection which compared pain levels according to IM injection sites (Güneş et al, 2013; Kara, 2013; Kilic et al, 2014; Rodríguez et al, 2017; Tuğrul & Khorshıd, 2014; Yilmaz et al, 2016) and many of these studies did not compare pain according to gender. Results similar to the findings of the present study were obtained in the limited number of comparison studies.…”
Section: Discussionmentioning
confidence: 99%